PARTIALLY REMOVABLE DENTURES - Ismoilov IIhomjon Xurboevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
As it follows from the practice of dentists and podiatrists a sufficiently large percentage of patients applies for rehabilitation after partial or total tooth loss. The article describes the types of dentures, though it is better to try to save one’s own natural teeth and not to bring the situation to critical state.